L-Theanine: A Unique Functional Amino Acid in Tea (Camellia sinensis L.) With Multiple Health Benefits and Food Applications - Li, Ming-Yue; Liu, Hong-Yan; Wu, Ding-Tao; Kenaan, Ahmad; Geng, Fang; Li, Hua-Bin; Gunaratne, Anil; Li, Hang; Gan, Ren-You (Frontiers in Nutrition, 2022)
Tea (Camellia sinensis L.) is a very popular health drink and has attracted increasing attention in recent years due to its various bioactive substances. Among them, L-theanine, a unique free amino acid, is one of the most important substances in tea. It not only influences the flavor of tea, but also has many health benefits and food applications. In order to provide updated information about L-theanine, this review summarized the influencing factors on L-theanine content in teas, the effects of L-theanine on tea flavor, the main health benefits and related mechanism of actions, and its food applications. The content of L-theanine in tea is affected by many factors, such as the cultivar, the growth period, as well as the climate. L-theanine is also an important factor affecting the quality of tea flavor. Moreover, L-theanine exhibits plenty of health benefits, such as antioxidant, anti-inflammatory, neuroprotective, anticancer, metabolic regulatory, cardiovascular protective, liver and kidney protective, immune regulatory, and anti-obesity effects. Therefore, due to the unique characteristics and beneficial functions, L-theanine should have potential applications in the development of functional foods with certain health benefits.